Exploring the disparities in park accessibility through mobile phone data: Evidence from Fuzhou of China. (1st March 2021) - Lin, Yuying; Zhou, Yanhai; Lin, Mingshui; Wu, Shidai; Li, Baoyin
Abstract: Parks are a major public service infrastructure for urban residents. Due to the unbalance geographic distribution of public parks within an urban, residents may have uneven access to this service. Despite there has been an efflorescent literature references, there is no consensus on how to properly measure the accessibility of park. The traditional place-based or infrastructure-based approach is often criticized for inappropriately defining spatial units or threshold distances. Taking a fast urbanization region-Fuzhou City, China as a case, this study overcomes this deficiency by employing the method of two-step floating catchment area (2SFCA) to evaluate the park accessibility using mobile phone data (during December 10, 2018 to December 16, 2018), which is people-based information with actual park users' origin-destination trajectory of park users. The results indicate that the threshold distance is 2 km from the visitors' home to park regardless of level, and the total number of visitors is relative fewer in weekend than that in workdays. The spatial distribution of park effective area presents a notably decreasing trend from the urban center to its periphery; however, the spatial distribution of park accessibility is more scattered and irregular. Finally, different key factors of park accessibility are identified for different locations using Geographically weighted regression (GWR) technique. Our study has a good implication for urban park planner and manager to implement differentiated planning policies for parks with full consideration of holistic factors. Highlights: User-based accessibility of public park was estimate mobile phone data. Threshold distance is 2 km from the visitors' home to park. The two-step floating catchment area (2SFCA) method was employed. Key factors of park accessibility were identified for each grid by GWR method.